A dynamic perspective on competition between traditional banking and banking fintechs - Chrzanowski, Marek; Dąbrowski, Ireneusz (Konkurencja pomiędzy tradycyjną bankowością a fintechami bankowymi w ujęciu dynamicznym, 2021)
The emergence of innovative financial services is having a huge impact on competition in the banking services market. The aim of the article is to show, from a dynamic perspective, the foundations of a model of competition occurring in the banking world between traditional financial institutions and fintechs. A dynamic two-sector model of competition is proposed with built-in feedback mechanisms in the form of demand side economies of scale. The model shows changes in market shares after a challenger enters a bank’s market with a portfolio of services as substitutes for the bank’s product offer. The traditional and new entities do not adjust the scope of their products over time, instead competing using those already available. The model obtained three economically significant steady states. Further analysis of the time path showed that the sector is heading towards an oligopolistic market structure in which both entities stabilize their market shares. However, in the event of low initial market penetration by traditional banks, a new innovative entity (a challenger bank) will completely dominate the sector, creating a monopolistic market structure
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 1-14